Adaptasi Tugas Seorang Akuntan dalam Era Pemulihan Ekonomi di Masa Covid-19 - Abdul Haris Kombih; Hendra Harmain; Laylan Syafina (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The COVID-19 pandemic has had a far-reaching impact on various economic sectors around the world. Accountants, as key players in the financial and business systems, face significant challenges in dealing with the profound changes taking place in the global economy. This study aims to investigate the adaptation of tasks performed by an accountant during the economic recovery amid the COVID-19 pandemic. This study focuses on the role of accountants in assisting companies, organizations and their clients to deal with the challenges and opportunities faced due to prolonged crisis situations. Through qualitative analysis and a review of the literature, this study identified a number of adaptation strategies adopted by accountants to overcome the challenges faced during the economic recovery during the pandemic. The three key findings are flexibility, technology and financial strategy. First, flexibility is an important quality that must be possessed by an accountant. The pandemic has caused rapid and unpredictable fluctuations in business situations, and accountants must be able to quickly adjust to these changes. The ability to make plans and change them according to changes in the environment is the key to surviving and adapting to uncertain circumstances. Second, technology has become an important tool in adapting accountants' duties during a pandemic. The use of high-tech accounting systems, financial applications, and virtual collaboration tools has become imperative for accountants to remain productive and efficient while working remotely. Technology also plays an important role in providing real-time access to financial data, which enables accountants to make informed and accurate decisions. Third, a smart financial strategy is key in helping companies and clients face the challenges of economic recovery. The accountant should act as a trusted financial advisor, providing in-depth insight into short and long term financial planning and assisting in identifying new opportunities for business growth. In addition, accountants must be able to develop effective risk management strategies, anticipate potential financial problems, and provide timely solutions.